Taxonomy Of Human Intelligence Development In Islam: Analysis Based On Majmū’āṯ Rasā’il Al-Imām Al-Ghazāli - Abdul Rahman, Siti Noor Mawar (2024)
Taxonomy is a study that examine in detail about entity, component and make a classification of it. There is also taxonomy which arrange the entity and component into a structure. The study of entity, component and structure of human intelligence is an ongoing studies and has provided many answers. No consensus achieves among scholars to define what human intelligence is and this effects its development. Therefore, taxonomy study is the solution to this puzzle. Taxonomy study through Islamic perspective is the paradigm shift in human intelligence scientific revolution. In midst of human intelligence’s inquiry, artificial intelligence (AI) merges as a challenge to human intelligence development. The development of AI seems to be moving progressively in replacing human intelligence and the direction of its movement is unknown. By using Islamic paradigm, the challenge of AI could be mitigated by introducing new paradigm of human intelligence through taxonomy study because new paradigm needs to answer all the basic questions. The objective of this taxonomy study is to identify basic entities, components and structural hierarchy of human intelligence development. The second objective is to analysze these basic entities, components and structural hierarchy based on collection of treatises or writings of al-Ghazālī (Majmū’aṯ Rasā’il al-Imām al-Ghazālī) abbreviated as MRIG. The third objective is to conclude the taxonomy of human intelligence development in Islam based on MRIG. This study is a basic qualitative design. Data is collected from primary and secondary data.